2011
DOI: 10.1039/c1cp21645g
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of computed signs and intensities for vibrational circular dichroism spectra

Abstract: We present in detail a novel measure that improves the reliability of the assignment procedure for vibrational circular dichroism (VCD) spectra extending the useful robustness concept introduced by Nicu and Baerends. This measure enables spectroscopists to single out bands with unreliable VCD intensities that can be disregarded during analysis and determination of absolute configuration. The previously proposed robustness criterion is shown to be gauge dependent and less reliable than the one proposed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 19 publications
1
83
0
Order By: Relevance
“…The higher of the two thresholds, T E and T C , will be selected to apply to both experimental and calculated DF/CID spectra in calculating the spectral similarity. For example, in measuring the VCD spectra the absolute values of vibrational dissymmetry factor (VDF) less than 10 ‐5 are not routinely measurable and calculated VDF magnitudes, using the criterion of Gobi and Magyarfalvi, less than 4x10 ‐5 may not be reliable . Thus, the use of gtrueν¯>4×105 consistently for both experimental and calculated VDF spectra would satisfy the robustness criteria for VDFs.…”
Section: Spectral Simulations and Analysismentioning
confidence: 99%
“…The higher of the two thresholds, T E and T C , will be selected to apply to both experimental and calculated DF/CID spectra in calculating the spectral similarity. For example, in measuring the VCD spectra the absolute values of vibrational dissymmetry factor (VDF) less than 10 ‐5 are not routinely measurable and calculated VDF magnitudes, using the criterion of Gobi and Magyarfalvi, less than 4x10 ‐5 may not be reliable . Thus, the use of gtrueν¯>4×105 consistently for both experimental and calculated VDF spectra would satisfy the robustness criteria for VDFs.…”
Section: Spectral Simulations and Analysismentioning
confidence: 99%
“…Since the rotatory strength (i.e., the intensity) of a VCD band is proportional to the scalar product of these values, angles close to 90° were supposed to indicate that even very small structural changes or small external perturbations can result in sign change for these vibrational modes. As shown later by the present authors, and Nicu and Baerends, this angle is gauge‐dependent, and, for example, this can lead to wrong classification of vibrational modes of large molecules, e.g., that of longer peptide chains. To overcome this problem an alternative gauge‐independent measure of the robustness has recently been suggested by some of the present authors, which utilizes the ratio between the rotational and the dipole strength, ζ k = R k /D k .…”
Section: Methods and Computational Detailsmentioning
confidence: 61%
“…Meanwhile, the spectrum of (L, L)‐ F1 gel also exhibited a negative signal and a positive signal at 1627 and 1635 cm −1 , thus suggesting the carbonyl groups of (L, D)‐ F1 and (L, L)‐ F1 should stack in a left‐handed manner. The VCD signals appeared in all the investigated region exhibited a vibrational dissymmetry factor (ΔA/A) within the order of 10 −3 to 10 −4 , which satisfied the criterion introduced by Góbi and Magyarfalvi and clearly indicated the reliability of VCD measurement according to the previous study of Zinna and Pescitelli . Overall, VCD study clearly demonstrated that the chirality of alanine at N ‐terminal determined the stacking chirality of carbonyl groups.…”
Section: Resultsmentioning
confidence: 98%